2006
DOI: 10.1084/jem.20052507
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for discrete stages of human natural killer cell differentiation in vivo

Abstract: Human natural killer (NK) cells originate from CD34(+) hematopoietic progenitor cells, but the discrete stages of NK cell differentiation in vivo have not been elucidated. We identify and functionally characterize, from human lymph nodes and tonsils, four NK cell developmental intermediates spanning the continuum of differentiation from a CD34(+) NK cell progenitor to a functionally mature NK cell. Analyses of each intermediate stage for CD34, CD117, and CD94 cell surface expression, lineage differentiation po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
504
3
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 382 publications
(555 citation statements)
references
References 33 publications
34
504
3
8
Order By: Relevance
“…The combination of CD11b and the TNF-receptor family member CD27 allows a further discrimination of NK-cell maturation stages. CD11b low iNK cells first express CD27 and then differentiate through a CD11b 1 CD27 1 to a CD11b 1 CD27 À stage that is considered to be the most mature [13,14,19,35]. We found that all ptCD56 bright express CD11b at the same high level as normal CD56 bright (for a representative example, see Fig.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…The combination of CD11b and the TNF-receptor family member CD27 allows a further discrimination of NK-cell maturation stages. CD11b low iNK cells first express CD27 and then differentiate through a CD11b 1 CD27 1 to a CD11b 1 CD27 À stage that is considered to be the most mature [13,14,19,35]. We found that all ptCD56 bright express CD11b at the same high level as normal CD56 bright (for a representative example, see Fig.…”
mentioning
confidence: 56%
“…Although some of the NK cells in SLO might be CD56 bright recirculating from the blood, others could represent early maturation stages of NK cells developing from hematopoietic precursor cells that repopulate extramedullary tissues and retain multi-lineage reconstitution capacity [16]. Caligiuri's group has identified lymphocytes in tonsils and lymph nodes representative of distinct stages of NK-cell development that differentiated into NK cells expressing high levels of CD56 [17][18][19]. NK-cell lineage commitment occurred in cells referred to as immature NK cells (iNK) that expressed no, or only very low levels of the NK-cell-associated markers NKp46, CD94, KIR and CD16.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although NK cells derive from marrow derived CD34 + cells [6,30], recent data support a role for differentiation in peripheral lymph nodes [46,47]. Although we and others have used the mouse feeder AFT024 to induce NK cell differentiation from CD34 + progenitors [25,48], here we show that EL08-1D2, another mouse microenvironment, is significantly better at recapitulating NK cell development.…”
Section: Discussionmentioning
confidence: 47%